Demanding child care: women's activism and the politics of welfare, 1940-71 - Fousekis, Natalie Marie (Women in American history, 2011)
Californians secure wartime child care -- Postwar hopes: the fight for permanent child care, 1945-47 -- Child care "is a state problem": working mothers and educators take action, 1947-51 -- "We need to stand together": Theresa Mahler, Mary Young, and the coalition's victory in the 1950s -- "We do not consider ourselves welfare cases": education-based child care and low-income working families, 1958-65 -- A different kind of welfare state: California's child care coalition in the age of protest, 1966-71